Investigations of a Micropower Thermoelectric Generator Operating at a Low Temperature Difference - Sateikis, I.; Ambrulevicius, R.; Lynikiene, S. (Elektronika ir Elektrotechnika, 2010)
The aim of the investigations is to carry out the energy evaluation of a micropower thermoelectric generator with natural heat transfer fluid circulation and low temperature difference. For the purpose of the investigations thermoelectric elements with the total area of 0.0096 m2 were used. The thermoelectric elements were installed between two flat-surfaced heat exchangers, through which both hot and cold heat transfer fluids flow. Temperature difference was 18.9 – 26.3 oC. The experiments showed that when the comparative cold water flow rate reaches 0.347-0.376 l/(s⋅m2), the amount of the power generated in 8 hours increases only marginally and comprises around 383 Wh/m2, while the coefficient of the generator efficiency amounts to around 1.1 %.